AI in Hidradenitis Suppurativa: Expert Evaluation of Patient-Facing Information - Ezanno AC; Fougerousse AC; Pruvost-Balland C; Maccari F; Fite C (Clinical, Cosmetic and Investigational Dermatology)
Anne-Cécile Ezanno,1 Anne-Claire Fougerousse,2 Christelle Pruvost-Balland,3 François Maccari,4 Charlotte Fite5 On behalf of ResoVerneuil1Department of Digestive, Surgery, Begin Military Teaching Hospital, Saint Mandé, France; 2Department of Dermatology, Begin Military Teaching Hospital, Saint Mandé, France; 3Department of Dermatology, University Hospital Pontchaillou, Rennes, France; 4Department of Dermatology, Begin Military Teaching Hospital, Saint Mandé and Medical Center, La Varenne Saint-Hilaire, France; 5Department of Dermatology, Saint Joseph Hospital, Paris, FranceCorrespondence: Anne-Cécile Ezanno, Department of Digestive, Surgery, Begin Military Teaching Hospital, Service de Chirurgie Viscérale – HIA BEGIN, 69 Avenue de Paris, St Mandé, 94160, France, Tel +33 (0)133985250, Fax: +33 (0)143985922, Email ezanno.annececile@gmail.comPurpose: This study investigates the accuracy of Artificial Intelligence (AI) chatbots, ChatGPT and Bard, in providing information on Hidradenitis Suppurativa (HS), aiming to explore their potential in assisting HS patients by offering insights into symptoms, thus possibly reducing the diagnostic and treatment time gap.Patients and Methods: Using questions formulated with the help of HS patient associations, both ChatGPT and Bard were assessed. Responses to these questions were evaluated by 18 hS experts.Results: ChatGPT’s responses were considered accurate in 86% of cases, significantly outperforming Bard, which only achieved 14% accuracy. Despite the general efficacy of ChatGPT in providing relevant information across a range of HS-related queries, both AI systems showed limitations in offering adequate advice on treatments. The study identifies a significant difference in the performance of the two AIs, emphasizing the need for improvement in AI-driven medical advice, particularly regarding treatment options.Conclusion: The study highlights the potential of AI chatbots, particularly ChatGPT, in supporting HS patients by improving symptom understanding and potentially reducing the time to diagnosis and treatment. AI chatbots, while promising, cannot yet substitute for professional medical diagnosis and treatment, indicating the importance of enhancing AI capabilities for more accurate and reliable medical information dissemination.Keywords: dermatology, hidradenitis suppurativa, acne inversa, artificial intelligence